RegioFEM – Informing future‐oriented flood risk management at the regional scale (Part I). Issue 1 (15th October 2021) - Löschner, Lukas; Eder, Markus; Herrnegger, Mathew; Hogl, Karl; Nordbeck, Ralf; Scherhaufer, Patrick; Schober, Bernhard; Seher, Walter; Wesemann, Johannes; Zahnt, Nina; Habersack, Helmut
Abstract: This contribution presents an integrated method to inform future‐oriented flood risk management across policy domains at the scale of river sections and (sub)catchments. The RegioFEM (Regional Floodplain Evaluation Matrix) combines approaches from hydrology, hydraulic engineering, spatial planning and stakeholder engagement to assess the dynamic changes in floodplains in consideration of projected investments in flood protection, expected settlement and infrastructure development and the likely climate‐induced changes in flood runoff. In this paper, we present the step‐by‐step approach of the RegioFEM, outlining how the method can be applied and replicated in practice in support of catchment‐oriented and forward‐looking flood management policies. The RegioFEM builds on the understanding of floodplains as coupled human and natural systems. It supports the simple comparative evaluation of the expected impacts of future developments in riparian areas on flood risk change and thus provides a basis to anticipate reciprocal effects between flood defence and land development to improve the sectoral interplay of integrated flood policies.